Serum and nasal lavage fluid eosinophil-derived neurotoxin levels and their determinants in adults - Saliha Selin Özuygur Ermis, MD; Carina Malmhäll, PhD; Magnus P. Borres, MD, PhD; Robert Movérare, PhD; Daniil Lisik, MD, PhD; Reshed Abohalaka, MSc; Selin Ercan, MD; Susanne Schmeisser; Rani Basna, PhD; Roxana Mincheva, MD, PhD; Göran Wennergren, MD, PhD; Jan Lötvall, MD, PhD; et al. (Journal of Allergy and Clinical Immunology: Global, 2025)
Background: Eosinophil-derived neurotoxin (EDN), an eosinophil granule protein, is a candidate biomarker in asthma to reflect eosinophilic activation. Objective: We sought to characterize the distribution of serum and nasal lavage fluid (NLF) EDN levels in different adult population subgroups and assess the determinants of high EDN levels. Methods: Serum and NLF samples were collected from a population-based adult cohort study, the West Sweden Asthma Study. In total, serum EDN was measured in 2939 subjects and NLF EDN in 878 subjects, both using ImmunoCAP (Phadia AB/Thermo Fisher Scientific, Uppsala, Sweden). High EDN levels were defined as values higher than the third quartile, derived from randomly selected general adult population. Background and clinical determinants of high EDN levels were assessed in serum and NLF samples. Results: Males had higher EDN levels than females, regardless of presence of asthma or atopy. EDN levels differed by obesity and atopy, but not by age, in the random adult population. Obesity was associated with high serum EDN levels in females (adjusted odds ratio [AOR], 1.81; 95% CI, 1.08-3.04) but not in males (AOR, 1.20; 95% CI, 0.63-2.29) in the random adult population. Subjects with current asthma were more likely to have higher serum EDN levels (AOR, 1.83; 95% CI, 1.55-2.17) than those without current asthma, but not higher NLF EDN levels. Conclusions: Adults with current asthma were more likely to have higher serum, but not NLF, EDN levels than those without asthma. Although serum EDN could be a promising marker in asthma, background determinants—such as sex, obesity, and atopy—should be considered when interpreting EDN levels.